Innovative nutrition: lyophilized and powdered bullfrog meat for use as a food supplement (Research, Society and Development, 2020)
Functional foods have aroused the interest of consumers, who seek, in addition to their basic function of nourishing, additional health benefits. The high biological value of bullfrog meat, the low fat content and the bioavailability of calcium, indicate its use as a functional food. Aiming at the practicality and feasibility of conservation, especially in strategic situations, the present work aimed to develop a technique to obtain a food supplement with powdered bullfrog meat, by means of grinding, freeze-drying and spraying. The nutritional, microbiological and physical-chemical results achieved demonstrated that this technology is feasible for the realization of sustainable and economic development, since it maintained cell integrity, showing similarity with the composition of fresh bullfrog meat, in addition to expanding its use over time, for at least eight months, for human consumption, according to the quality control carried out, generating an innovative product for future industrial uses. As a functional food it will be available in more conservative forms, such as encapsulations and dry packaging. Therefore, a product was prepared with the promise of being an excellent supplement, being able to supply nutritional deficiencies by the quality of its protein, in addition to being a protein base of easy transport and consumption, with food safety.